Vacuolization in embryos on days 3 and 4 of in vitro development: Association with stimulation protocols, embryo development, chromosomal status, pregnancy and neonatal outcomes - Chen, Longbin; Zhang, Shuoping; Gu, Yifan; Peng, Yangqin; Huang, Zenghui; Gong, Fei; Lin, Ge (Frontiers in Endocrinology, 2022)
Study question Is vacuolization in embryos on Days 3 and 4 associated with parent-related factors, stimulation protocols, embryo development, embryo ploidy, pregnancy and neonatal outcomes? Study design, size, duration This is a retrospective cohort study that comprised 5,703 embryos from 611 patients who underwent preimplantation genetic testing and time-lapse monitoring of their embryos from August 2017 to September 2021. Main results Embryo vacuolization on Days 3 and 4 is associated with the LH level on the day of the hCG trigger and the number of retrieved oocytes. Compared to vacuole-negative embryos, the rates of blastocyst formation and good-blastocyst formation was significantly lower in vacuole-positive embryos. We observed no significant difference in the rates of euploidy, implantation, ongoing pregnancy, and live birth between vacuole-positive and vacuole-negative embryos. In vacuole-positive embryos, the embryos of which the vacuole-positive blastomeres were involved in embryo compaction exhibited significantly higher mosaicism rate compared with those of which the vacuole-positive blastomeres were not involved in embryo compaction. Conclusion Vacuolization in embryos on Days 3 and 4 is associated with reduced blastocyst formation rate and high-quality blastocyst rate. Blastocysts had a low mosaicism rate if the vacuole-containing cells were rejected in compaction process, which supports the hypothesis that exclusion of abnormal blastomeres from compaction is a self-correction mechanism.